2004
DOI: 10.1016/j.orthres.2003.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular quadriceps dysfunction prior to osteoarthritis of the knee

Abstract: Decreased maximal quadriceps strength and voluntary activation has been observed in patients with osteoarthritis in previous studies, but those results d o not allow any conclusions to be drawn as to whether quadriceps dysfunction precedes or follows osteoarthritis. Thirty-two patients (group a) who underwent partial ineniscectomy 48 k 9 month prior to the study were matched according to their weight and body mass index with a control group (group b). The twitch interpolation technique was used to determine ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
98
1
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(106 citation statements)
references
References 48 publications
(45 reference statements)
4
98
1
3
Order By: Relevance
“…Each wavelet was represented by a bell shaped filter curve in frequency space and had a short wave as a counterpart in time space. The wavelets were characterized by their center frequency (Hz), bandwidth (Hz), and time resolution (ms): wavelet 0 (7 Hz, 15 ). An interpolation was used to convert noninteger wavelet numbers (e.g., mean wavelet number) to frequencies.…”
Section: Emg Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Each wavelet was represented by a bell shaped filter curve in frequency space and had a short wave as a counterpart in time space. The wavelets were characterized by their center frequency (Hz), bandwidth (Hz), and time resolution (ms): wavelet 0 (7 Hz, 15 ). An interpolation was used to convert noninteger wavelet numbers (e.g., mean wavelet number) to frequencies.…”
Section: Emg Measurementmentioning
confidence: 99%
“…6,8,[15][16][17][18][19][20][21] It has been shown that in knee OA the quadriceps strength is usually reduced by 14% to 45% compared to control subjects. 6,8,18,19,21 Sirca et al 22 reported that degenerative hip OA was associated with an atrophy of type II fibers.…”
Section: Introductionmentioning
confidence: 99%
“…5 In addition to the effects on the joint structure and function, OA also has a negative effect on the musculoskeletal system. Patients with knee OA have decreased knee extensor strength compared to healthy subjects [6][7][8][9][10] and compared to the healthy contralateral limb. 11,12 Evidence also suggests that the muscle weakness is associated with a decrease in muscle mass.…”
mentioning
confidence: 96%
“…4 Altered biomechanics and neuromuscular control have been postulated to play a significant role in the disproportionate incidence of knee joint injuries and osteoarthritis observed in females. 5,6 Consequently, researchers have recently placed significant effort into elucidating neuromuscular and biomechanical differences in males and females. Although researchers have evaluated gender differences in muscle responses to destabilizing loads applied to the joint and knee kinematics and kinetics during sport specific activities, [7][8][9][10][11] it remains unclear whether there are fundamental differences in the voluntary knee muscle control strategies used by athletic males and females.…”
mentioning
confidence: 99%